INNOVATION OF CNC MACHINERY PROGRAMMING EDUCATION AT THE FACULTY OF TECHNOLOGY - Koleda, Peter; Koleda, Pavol; Barcík, Štefan (Innovation in Woodworking Industry and Engineering design, 2020)
The paper describes the educational project ending in 2020, which is focused on increasing the quality of teaching and making the study more attractive by introducing new selective courses: CNC technology in bachelor study programs and Programming of CNC technology in engineering study programs at the Faculty of Technology of the Technical University in Zvolen, Slovakia. The solution of the project is also to create a background for building a CNC machining workplace. The article summarizes the educational machinery for teaching especially milling operations. Teaching programming takes place in professional CNC emulators that are commonly used in praxis. These emulators allow program debugging, tests, trajectory drawing and optimising and collision checking of tool and workpiece. Altogether 23 students successfully completed the introduced course. Within the project solution, 5 theses were defended.